Strategies Used by Professional Interpreter in Indonesian-English Simultaneous Interpreting (ELS Journal on Interdisciplinary Studies in Humanities, 2023)
The practice of simultaneous interpreting presents complex challenges due to its immediate nature and the need for prompt responses. Simultaneous interpreters are required to perform their tasks immediately in order to match the speaker’s pace. This may lead to information overload and difficulties in dealing with complex sentence structures or specialized terminology. In order to overcome the challenges encountered in simultaneous interpreting, interpreters employ a range of interpreting strategies. This study aims to investigate the strategies applied by a professional interpreter in the YouTube video entitled “Simultaneous Interpreting Example”. Qualitative method was applied in this study and the data was collected through observation and note-taking. The data was analyzed by applying the theory of interpreting strategies proposed by Li (2015). The result of the study revealed that there were six interpreting strategies employed by the interpreter in the video, namely addition, paraphrasing, compression, omission, segmentation, and restructuring. Addition is the most dominant strategy applied, followed by paraphrasing, and compression. These strategies enabled the interpreter to adapt to distinct language structures, improve audience comprehension, and efficiently convey complex ideas in cross-linguistic communication.
Keywords: Interpreting; Simultaneous; Strategies